Impact of Postfault Active Power Recovery of Photovoltaic Power Generation on Transient Stability. Issue 4 (March 2017) - KAWABE, KENICHI; MATSUDA, ISSEI; TANAKA, KAZUYUKI
SUMMARY: Currently, Japanese grid codes require photovoltaic (PV) power generation systems to continue supplying power to the grid as soon as possible even if the systems temporarily stop their operation. Although the fault ride‐through capability was originally proposed for preventing a cascading frequency drop in the power system, the capability has the impact on other instability phenomena such as transient stability. In this study, we focus on the postfault active power recovery of the PV systems. The impact of the recovery speed on the transient stability is investigated under different load conditions, in particular static/dynamic load condition. Numerical examples are carried out for the one‐machine one‐load infinite‐bus system, and the effects of the recovery speed are evaluated by equal area criterion and critical clearing time. As a result, we have found both desirable and undesirable effects on the transient stability depending on the load condition.